Analisis Beban Kerja dengan Metode Work Load Analysis pada Departemen Produksi di PT. X - Al-Muqaffa, Figar Wafiq; Yohanes, Ricky; Winarsih, Neneng (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Determination of the workload given by the company to employees must be considered. The workload analysis method is used to calculate the workload of a particular function within the company. This research was conducted at PT. X is engaged in special chemicals for various industries, ranging from paper, rubber, food, agriculture, oil mining, cosmetics and other industries. Therefore it is necessary to analyze the workload of employees in the production department because it is directly related to production activities carried out while working. The results of the identification of workload analysis based on the job description along with the hoursworked by employees and the determination of allowances (free time) show that production department employees have workloads, namely the production admin section with 1 employee by 79%, production foreman with 1 employee by 89%, and production operators with 1 employee by 82%, this shows that the workload provided is still in a safe condition. Keywords: Allowance, Ergonomics, Work Load Analysis